Quality control of Hypericum perforatum L. analytical challenges and recent progress. (7th March 2017) - Agapouda, Anastasia; Booker, Anthony; Kiss, Tivadar; Hohmann, Judit; Heinrich, Michael; Csupor, Dezső
Abstract: Objectives: The most widely applied qualitative and quantitative analytical methods in the quality control of Hypericum perforatum extracts will be reviewed, including routine analytical tools and most modern approaches. Key findings: Biologically active components of H. perforatum are chemically diverse; therefore, different chromatographic and detection methods are required for the comprehensive analysis of St. John's wort extracts. Naphthodianthrones, phloroglucinols and flavonoids are the most widely analysed metabolites of this plant. For routine quality control, detection of major compounds belonging to these groups seems to be sufficient; however, closer characterization requires the detection of minor compounds as well. Conclusions: TLC and HPTLC are basic methods in the routine analysis, whereas HPLC‐DAD is the most widely applied method for quantitative analysis due to its versatility. LC‐MS is gaining importance in pharmacokinetic studies due to its sensitivity. Modern approaches, such as DNA barcoding, NIRS and NMR metabolomics, may offer new possibilities for the more detailed characterization of secondary metabolite profile of H. perforatum extracts.